AB0554 Expression of Serum B Cell Activating Factor from the Tumour Necrosis Factor Family (BAFF) and A Proliferation-Inducing Ligand (APRIL) in Systemic Lupus Erythematosus: Relationship with Disease Activity. (10th June 2014) - Panafidina, T.; Sokhova, M.; Verizhnikova, Z.; Novikov, A.; Alexandrova, E.; Popkova, T.; Solovyev, S.; Nasonov, E.
Abstract : Background: The B lymphocyte stimulator signaling pathway by BAFF and its homologue APRIL has an important role in the selection, maturation and survival of B cells and plays a significant role in the pathogenesis of systemic lupus erythematosus (SLE). Objectives: The aim of the study is to evaluate BAFF and APRIL in patients with SLE. Methods: The 30 pts (80% female, age 31, 0 [28, 0-45, 0 years] (mediana [interquartile range 25%>75%])) with SLE (ACR criteria, 1982) and 27 controls (93% female without any rheumatic and infectious diseases, age 27, 0 [26, 0-30, 0] years) were examined. We considered SLE-related factors: disease duration, clinical features, SLE Disease Activity Index (SLEDAI 2K), Systemic Lupus International Collaborating Clinics (SLICC) damage index and treatment. All patients were evaluated for laboratory data (ESR, CRP, immunoglobulin G, A and M, complement fragments C3 and C4 and others), autoantibodies (ANA, antiDNA, ENA-SSA, -SSB, -Sm, aPL) and CD19 B lymphocytes subpopulation. The concentration of soluble BAFF and APRIL (ng/ml) were determined in serum samples by ELISA (Bender MedSystem GmbH, Austria). B cells were detected by flow cytometry. Statistical analysis has been performed with STATISTICA program, version 8.0. Results: The mean disease duration of SLE was 7, 0 [2, 0-10, 0] years, SLEDAI 2K score - 4 [2-13], SLICC damage index score - 0 [0-1], current prednisone dose – 10, 0 [7, 5-25, 0] mg/day. SLE pts did not differ from healthy controls in BAFF (0, 02 [0, 02-0, 08] vs 0, 02 [0, 02-0, 02] ng/ml) and APRIL (0, 01 [0, 01-0, 62] vs 0, 01 [0, 01-0, 01] ng/ml) levels. Among SLE pts BAFF level correlated with lupus anticoagulant (r=0, 88, p<0, 05) and ESR (r=0, 43, p<0, 05); APRIL level correlated with SLEDAI 2K (r=0, 55, p<0, 01), CRP (r=0, 50, p<0, 01), antiDNA (r=0, 38, p<0, 05), creatinine level (r=0, 39, p<0, 05), current prednisone dose (r=0, 55, p<0, 01) and CD19 B lymphocytes absolute count (r=0, 89, p<0, 05). We divided SLE pts on two groups: the 1st- pts with high activity (SLEDAI 2K≥8), the 2nd – pts with low (SLEDAI 2K<8). The patients of 1st group had higher level of APRIL (1, 69 [0, 01-4, 0] vs 0, 01 [0, 01-0, 01] ng/ml, p<0, 05) compared to 2nd group and control, there is no difference in BAFF level in these groups. Conclusions: In our study there are no differences in BAFF and APRIL levels in patients with SLE and healthy control. This result may be explained by successful therapy and suppression of disease activity in our patients. Patients with high activity of SLE had increased level of APRIL, there is no correlation in disease activity and BAFF level. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3582